PENINGKATAN KOMPETENSI PENDIDIK DALAM PENYUSUNAN MODUL BAHAN AJAR DI YAYASAN ISKANDARIYAH TANGERANG SELATAN - Edi Junaedi; Turkamun Turkamun; Deni Darmawan; Sapto Hadi Imambachri; Ismul Bathni Sumadikarta (PENGABDIAN SOSIAL, 2022)
ABSTRACTThe teaching materials module is one consequence of the implementation of the Competency-Based Education Unit Level Curriculum in schools. The competency approach requires the use of teaching materials modules in the implementation of learning. This teaching material module can assist schools in realizing quality learning and having uniformity in the delivery of subject matter from educators to all students. The application of the teaching material module can condition learning activities to be better, planned, directed, independent, complete and with optimal results in accordance with the initial target and according to the expectations of the school/foundation. Teaching Materials Module is material that is systematically arranged in language that is easily understood by students according to their age and level of knowledge, with the aim that they (students/students) can study independently even with minimal guidance from educators (Andi Prastowo, 2012: 106). The module is a program package that is structured and designed in such a way as a material and reference for student learning and as a teaching reference for all educators. With the Teaching Materials Module, it is hoped that the student's learning process can be independent and also to help students more easily master their learning objectives. Therefore, students can learn according to their respective absorption and capture power. Our intention and purpose of conducting PKM (Community Service) by providing guidance on the preparation of Teaching Materials at the Iskandariyah Ciputat Foundation is based on our desire to play an active role in building a strong and good quality education so that it can provide satisfaction for teachers, students, staff, parents, and the surrounding community in general, whose ultimate goal is that the Iskandariyah Ciputat Education Foundation, South Tangerang, can improve the quality of the learning process, improve the quality of schools in general and be able to produce quality graduates in welcoming the world of work.  ABSTRAK Modul bahan ajar adalah salah satu konsekuensi diterapkannya Kurikulum Tingkat Satuan Pendidiakn Berbasis Komptensi di sekolah. Pendekatan kompetensi mempersyaratkan penggunaan modul bahan ajar dalam pelaksanaan pembelajarannya. Modul bahan ajar ini dapat membantu sekolah dalam mewujudkan pembelajaran yang berkualitas dan memiliki keseragaman dalam penyampaian materi pelajaran dari tenaga pendidik kepada seluruh siswa/siswinya. Penerapan modul bahan ajar dapat mengkondisikan kegiatan pembelajaran lebih baik, terencana, terarah, mandiri, tuntas dan dengan hasil (output) yang optimal sesuai dengan target awal dan sesuai harapan pihak sekolah/yayasan. Modul Bahan Ajar merupakan materi yang disusun secara sistematik dengan bahasa yang mudah dipahami oleh siswa sesuai usia dan tingkat pengetahuan mereka, dengan tujuan agar mereka (siswa/siswi) dapat belajar secara mandiri walaupun dengan tingkat bimbingan yang minim dari pendidik (Andi Prastowo, 2012 : 106). Modul merupakan paket program yang disusun dan didesain sedemikian rupa sebagai bahan dan acuan belajar siswa dan sebagai acuan mengajar semua tenaga pendidik. Dengan adanya Modul Bahan Ajar diharapkan proses belajar siswa bisa mandiri dan juga untuk membantu siwa lebih mudah menguasai tujuan belajarnya. Oleh karena itu, siswa  dapat belajar sesuai dengan daya serap dan daya tangkap masing-masing. Maksud dan tujuan kami melakukan PKM (Pengabdian Kepada Masyarakat) dengan memberikan pembinaan tentang penyusunan Bahan Ajar di Yayasan Iskandariyah Ciputat ini didasari oleh keinginan kami untuk ikut berperan aktif dalam membangun kualitas pendidikan yang kuat dan baik sehingga dapat memberikan kepuasan bagi guru, siswa/siswi, staf, orang tua siswa, serta masyarakat sekitar       pada umumnya, yang tujuan akhirnya agar Yayasan Pendidikan Iskandariyah Ciputat Tangerang Selatan dapat meningkatkan mutu proses pembelajaran, meningkatkan mutu sekolah secara umum dan mampu menghasilkan lulusan yang berkualitas dalam menyongsong dunia kerja.